Comportamento dos custos de produção do café arábica em relação aos fatores climáticos - Rodrigues, Núbia Aparecida (2013)
Arabica coffee production cost management faces challenges due to the diversity of factors that affect its formation within farms. Among the various factors that interfere in arabica coffee production costs formation, climatic factors stand out, especially temperature and precipitation conditions. The coffee plant is different from other fruit plants because it needs two years to complete its full reproductive cycle; that means flowering and fructification do not occur in the same calendar year. Such peculiarity made researchers divide the phenological cycle of the coffee plant into phenological phases, so as to facilitate the understanding of the climatic requirements of the plant. These phases are: (1) vegetation and formation of leaf buds, (2) induction and maturation of flower buds, (3) flowering, pelleting and fruit expansion, (4) graining, (5) maturation, and (6) rest. Climatic condition behavior patterns during each of these phases interfere directly in the productive performance of the plant. Theoretical review points out that the productivity of the crop affects the formation of the production costs of the crop. Thus, the aim was to investigate arabica coffee production cost behavior in relation to the climatic factors during the phenological phases of the coffee plant. The sample in this study was made of the major cities in the main production regions in the country, from 2003 to 2012. The most representative activity cost components within this period of time were manpower, machinery operations, fertilizers, pesticides, agricultural chemicals, and other items. The behavior of these components was observed in relation to temperature and precipitation conditions. The descriptive and quantitative analysis in this study was developed in three stages. The first stage presented production cost composition and behavior of temperature and humidity conditions for the period of time studied. The second stage used simple correlation (r) to investigate the behavior of arabica coffee production costs related to the climatic factors in each place studied. Finally, the backward method multiple linear regressions (R2) were used to search for a relation between production costs and climatic factors for all the cities altogether. During the first stage the cities with higher temperatures and differential rainfall indices within the period studied were those with higher final production costs. In associating arabica coffee production costs with climatic factors, the simple correlation analyses (r) highlighted the importance of temperature and humidity conditions in the phenological phases of flower bud induction, maximum vegetation, and graining. This result is similar to the one found by Weill et. al. (1999) and Arruda et. al. (2000,) who investigated coffee plant production in relation to climatic factors. The results of the multiple linear regressions (R2) presented waste autocorrelation problems and multicollinearity, and therefore need further investigation. The relevance of this study is mainly associated to the theoretical contribution of the behavior of arabica coffee production costs in relation to climatic factors, due to the scarcity of studies of such nature.